Is Marital Status a Predictor of Job Satisfaction of Public Secondary School Teachers - Mocheche, Esther Kemunto; Raburu, Pamela Adhiambo; Bosire, Joseph (International Journal of Psychology and Behavioral Sciences, 2018)
Job satisfaction is a globally important factor in determining human capital and subsequent worker productivity.In Kenya, human capital is a major concern as evidenced by teacher burnout and the strikes in the teaching fraternity. This study investigated the influence of marital status on job satisfaction of public secondary school teachers in Kisii Central Sub-County, Kenya. Maslow’s hierarchy of needs and Herzberg’s two factor theories guided the present study. The study’s target population consisted all 903 public secondary school teachers in Kisii Central Sub County. A sample of 306 was selected by stratified random sampling to obtain a sample that was representative from all the categories of secondary schools followed by stratification according to gender. For qualitative data, twelve secondary school principals were purposively selected. The study adopted a convergent parallel research design with mixed method research approach. Data collection tools were questionnaires (modified Sorensen self-esteem scale and job descriptive index) and interview schedule. Validity was ensured by the assistance of the two supervisors’ judgment. Reliability coefficient was computed using Cronbach’s Alpha and it was found to be 0.764. Quantitative data was organized using the Statistical Package for Social Sciences (SPSS) version 20.0 and the data was analyzed using both descriptive and inferential statistics. Qualitative data was analyzed using Thematic analysis. It was established that marital status had an influence on job satisfaction where the married were much happier in their jobs than the single. [F (4, 257) = 3.62, p=0.007.]. The study recommended that teacher counsellors should adopt appropriate cognitive behavioral therapy techniques to assist divorced and single teachers enhance their self-esteem and job satisfaction. This study recommends further research in gender and efficacy school management among secondary school principals.
Keywords: Job satisfaction; Marital status; Married; Divorced; Widowed; Separated; single